Controls of H2S, Fe2 +, and Mn2 + on Microbial NO3–-Reducing Processes in Sediments of an Eutrophic Lake - Cojean, Adeline N. Y.; Lehmann, Moritz F.; Robertson, Elizabeth K.; Thamdrup, Bo; Zopfi, Jakob (Frontiers in Microbiology, 2020)
Understanding the biogeochemical controls on the partitioning between nitrogen (N) removal through denitrification and anaerobic ammonium oxidation (anammox), and N recycling via dissimilatory nitrate (NO3-) reduction to ammonium (DNRA) is crucial for constraining lacustrine N budgets. Besides organic carbon, inorganic compounds may serve as electron donors for NO3- reduction, yet the significance of lithotrophic NO3- reduction in the environment is still poorly understood. Conducting incubation experiments with additions of 15N-labeled compounds and reduced inorganic substrates (H2S, Fe2+, Mn2+), we assessed the role of alternative electron donors in regulating the partitioning between the different NO3--reducing processes in ferruginous surface sediments of Lake Lugano, Switzerland. In sediment slurry incubations without added inorganic substrates, denitrification and DNRA were the dominant NO3--reducing pathways, with DNRA contributing between 31% and 46% to the total NO3- reduction. The contribution of anammox was less than 1%. Denitrification rates were stimulated by low to moderate additions of ferrous iron (Fe2+ ≤ 258 µM) but almost completely suppressed at higher levels (≥ 1300 µM). Conversely, DNRA was stimulated only at higher Fe2+ concentrations. Dissolved sulfide (H2S, i.e. sum of H2S, HS- and S2-) concentrations up to ~ 80 µM, strongly stimulated denitrification, but did not affect DNRA significantly. At higher H2S levels (≥ 125 µM), both processes were inhibited. We were unable to find clear evidence for Mn2+-supported lithotrophic NO3- reduction. However, at high concentrations (~ 500 µM), Mn2+ additions inhibited NO3- reduction, while it did not affect the balance between the two NO3- reduction pathways. Our results provide experimental evidence for chemolithotrophic denitrification or DNRA with Fe2+ and H2S in the Lake Lugano sediments, and demonstrate that all tested potential electron donors, despite the beneficial effect at low concentrations of some of them, can inhibit NO3- reduction at high concentration levels. Our findings thus imply that the concentration of inorganic electron donors in lake sediments can act as an important regulator of both benthic denitrification and DNRA rates, and suggest that they can exert an important control on the relative partitioning between microbial N-removal and N-retention in lakes.